EKSISTENSI KEPEMIMPINAN TRANSFORMASIONAL PENDIDIKAN ISLAM DI ERA DIGITAL - Siswadi (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to analyze the presence of transformational leadership in Islamic education in the digital age. Transformational leadership is viewed as a leadership model capable of inspiring, motivating, and guiding positive change within Islamic educational institutions, particularly in addressing the challenges and opportunities presented by advancements in digital technology. The research method employed is a literature review, examining various relevant academic sources such as books, articles, and journals. The findings indicate that transformational leadership plays a strategic role in shaping a vision for Islamic education that is adaptable to the digital age, enhancing the quality of technology-based learning, and reinforcing spiritual and moral values amidst the tide of globalization. Furthermore, transformational leadership contributes to fostering a culture of innovation, collaboration, and the integration of information technology into the educational process. In conclusion, the presence of transformational leadership in Islamic education in the digital age is not only crucial for the sustainability of educational institutions but also serves as a key factor in nurturing a generation that is principled, competitive, and of noble character.